2014
DOI: 10.1371/journal.pone.0096164
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Variations in the Rates of Hospital Complications, Failure-to-Rescue and 30-Day Mortality in Surgical Patients in New South Wales, Australia, 2002-2009

Abstract: BackgroundDespite the increased acceptance of failure-to-rescue (FTR) as an important patient safety indicator (defined as the percentage of deaths among surgical patients with treatable complications), there has not been any large epidemiological study reporting FTR in an Australian setting nor any evaluation on its suitability as a performance indicator.MethodsWe conducted a population-based study on elective surgical patients from 82 public acute hospitals in New South Wales, Australia between 2002 and 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…We did not observe any differences between NSW hospital peer groups for VTE mortality, neither other studies did for FTR rates. 45 However, we did observe greater variation in VTE mortality within peer groups comprising smaller sized hospitals in comparison to larger principal referral hospitals.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…We did not observe any differences between NSW hospital peer groups for VTE mortality, neither other studies did for FTR rates. 45 However, we did observe greater variation in VTE mortality within peer groups comprising smaller sized hospitals in comparison to larger principal referral hospitals.…”
Section: Discussionmentioning
confidence: 48%
“…25 Based on our findings, VTE incidence and associated mortality contributes to approximately 15% and 8% of overall FTR-related incidence and mortality (13.8 and 140 per 1000 patients, respectively). 45 46 Despite the fact that our study and the US study used the identical measure defined by AHRQ, 23 the discrepancies and coding practices between the USA (ICD-9-CM) and Australia (ICD-10-AM) may, in part, have contributed to the difference. It was shown that accuracy of VTE coding can be improved by the adoption of extended codes developed in the revised ICD-9-CM.…”
Section: Discussionmentioning
confidence: 91%
“…Others tried to identify the influence of characteristics and size of hospitals with adverse events rates or issues of the HAI program, with heterogeneous results. 10,19,20 The results from this study showed that the HAIPCC tend to have a balanced level of compliance between the 4 main components of the program. The findings that hospitals that are more compliant with HAIPCC tend to have also high compliant SSs may be explained by the mutual influence between nurses in SSs and the HAIPCC.…”
Section: Discussionmentioning
confidence: 64%
“…Variation in performance [ 43 , 44 ], quality and safety [ 45 , 46 ] and service usage [ 47 ] indicators among acute care providers in NSW and elsewhere has been identified. Taking into account patient and admission differences, notable inter-hospital variability in discrepancy incidence rates was evident among 80 NSW public hospitals.…”
Section: Discussionmentioning
confidence: 99%